Multi-spectroscopic and molecular docking studies on the interaction of new phthalimides with calf-thymus DNA: In vitro free radical scavenging activities. Issue 2 (7th February 2016) - Nayab, Pattan Sirajuddin; Pulaganti, Madhusudana; Chitta, Suresh Kumar; Rahisuddin,
ABSTRACT: In this study, we report the synthesis and biological evaluation of novel phthalimide based Schiff base derivatives as promising antioxidant and DNA-binding agents. The structural investigation of the synthesized compounds was determined by spectral and elemental analysis. In vitro DNA-binding studies of title compounds were carried out by UV–Vis, fluorescence, circular dichroism spectroscopic techniques, cyclic voltammetry, thermal denaturation studies, and hydrodynamic measurements to investigate their potential as DNA-binding agents. The DNA binding constant ( K b ) of target compounds was obtained from absorption studies between 1.2 × 10 5 M −1 and 1.27 × 10 5 M −1, respectively, suggesting that the test compounds have shown good affinity toward calf-thymus DNA. The experimental results of DNA-binding studies reveal a non-intercalative mode of binding between DNA and the synthesized compounds, most probably groove binding. In addition, molecular docking techniques were performed to rationalize the observed binding affinities with the target DNA. Furthermore, antioxidant and free radical scavenging activities of the synthesized compounds were carried out to find out their pharmacological potential. The results indicate that the title compounds displayed good antioxidant activity against DPPH (IC50 : 0.727 and 0.656 mg/mL) and H2 O2 radicals (IC50 : 1.072 and 0.911 mg/mL) comparable to standard ascorbic acid.